Avaliação da cisteína adicionada ao meio diluente sobre espermatozoides ovinos mantidos fresco, refrigerado e congelado - Corandin, Eduardo Mazon (2013)
The use of frozen semen is a practice still little spread among the sheep producers and shows pregnancy results unsatisfactory. Because this the addition of antioxidant in the extenders to improve the sperm quality after your handing is the goal of many researchers. Therefore, the aim of this study was to analyze in vitro effects of different concentrations of cysteine anti-oxidant in extenders on the sheep sperm storage fresh, cooled and frozen. After sperm sampling and the individual analysis, the semen of six-sheep were pooled and divided in equal aliquots to be diluted in PBS (fresh semen), Equimix® (cooled semen) or Bovimix® (frozen semen). For each of these groups were added cysteine in different concentrations 0, 2.5, 5.0 and 7.5 mM, so were made the respective experimental groups Control, Cys2.5, Cys5.0 and Cys7.5. The fresh semen was stored in room temperature during two hours, the cooled semen was stored among four to eight hours in 16ºC and the frozen semen was stored into liquid nitrogen. The analyzed variables to the fresh and cooled semen were motility, vigor, viability and mitochondrial potential of the spermatozoids. To the frozen semen, the parameters evaluated were the plasmatic and acrossomal membranes integrity, kinect by the computer system (CASA) and the mitochondrial potential. The group Cys7.5 showed the highest values of motility in the fresh semen (73.50%), however there was not different (p>0.05) than the group Cys5.0 in the cooled semen after four (68.00 vs 66.50%) and eight hours (57.00 vs 55.00%). For the frozen semen, the addition of 7.5 mM cysteine promoted the highest percentage of spermatozoids with integrate plasmatic membrane (23.2%), followed by the Cys5.0 group (20.0%), however there was not statistic different (p<0.05) among the group in the acrosomal integrity. The addition of cysteine in the frozen extender promoted increased in the capacity of mobility to the spermatozoa. There was not difference (p>0.05) among the groups Cys5.0 and Cys7.5 mM for the variables average-path (VAP), straight-line (VSL) and curvilinear velocity (VCL), however the concentration of 7.5 mM cysteine was more efficient in the protection of plasmatic membrane and increased the beat/cross frequency (BCF).